COVID-19 in Association With Development, Course, and Treatment of Systemic Autoimmune Rheumatic Diseases - Lakota, Katja; Perdan-Pirkmajer, Katja; Hočevar, Alojzija; Sodin-Semrl, Snezna; Rotar, Žiga; Čučnik, Saša; Žigon, Polona (Frontiers in Immunology, 2021)
Autoimmune diseases and infections are often closely intertwined. Persons with autoimmune diseases are more susceptible to infections due to either active autoimmune disease or the medications used to treat them. Also, based on infections as environmental triggers of autoimmunity, an autoimmune response would also be expected in COVID-19. Although some studies have shown the emergence of autoantibodies and the potential development of autoimmune diseases after SARS-CoV-2 infection, current data suggest that the levels of autoantibodies following SARS-CoV-2 infection is comparable to that of some other known infections, and that autoantibodies might only be transient. The risk of SARS-CoV-2 infection in patients with a systemic autoimmune rheumatic disease (SARD) appears slightly higher compared to the general population and the course of COVID-19 disease does not seem to be very different, however, specific therapies such as glucocorticoids and anti-TNF might contribute to risk of hospitalization/death. Cytokine release syndrome is a severe complication in COVID-19. Many drugs used for the treatment of SARD are directly or indirectly targeting cytokines involved in the cytokine release syndrome, therefore it has been suggested that they could also be effective in COVID-19. So far, there is no evidence that any specific immunomodulatory drug used for the treatment of SARD protects against a more severe course of COVID-19, but more evidence on the use of these medications for the treatment of COVID-19 is currently being collected.